How do foreign customers' perceptions of product-harm crises affect their transfer of capability- and character-based stigma?. Issue 1 (30th December 2021) - Xue, Rui; Qian, Gongming; Qian, Zhengming; Li, Lee
Abstract : Purpose: Customers often trace a product-harm crisis to the deviant firm's capability- or character-relevant issues. This study examines how capability- and character-based stigma associated with product-harm crises influence foreign customers' product preferences (i.e. brand affect and purchase intention) for other firms from the same country of origin. Design/methodology/approach: Qualitative survey data are used to test hypotheses with a structural equation model. Findings: The authors find that negative capability judgment significantly affects foreign customers' product preferences for other firms from the same country of origin, whereas negative character judgment does not. However, customers' national animosity and product knowledge moderate the stigma spillover effects. Specifically, national animosity and product knowledge weaken the spillover effects of capability-based stigma but strengthen those of character-based stigma. Research limitations/implications: Future research could examine strategies for uninvolved firms to avoid the stigma-by-association effect. Moreover, due to the lack of resources to collect data, this study does not investigate how customers' generalized favorability and familiarity with crisis-stricken firms and uninvolved firms moderate the stigma-by-association effect. Originality/value: The findings of this study advance our knowledge on product-harm crises and the stigma-by-association effect.